2020
DOI: 10.21203/rs.3.rs-22354/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new view into the silica deposition vesicles of diatoms

Abstract: Abstract Diatoms are single-celled microalgae that produce silica-based cell walls with intricate nano- and micropatterns. Biogenesis of diatom biosilica is a bottom-up process that occurs in large intracellular compartments termed silica deposition vesicles (SDVs). Investigating the mechanism of silica morphogenesis has so far been severely limited by the lack of methods for imaging the entire volume of an SDV with high spatial resolution during all stages of developme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The extraordinary precision and frequency with which this mechanism occurs has always fascinated and intrigued biologists and different models have been proposed. However, to date none of them is able to explain biosilica morphogenesis in its entirety [109]. Indeed, there are still many components of the process that should be clarified, such as how this higher-order structure is formed and what are the exact spatial and temporal mechanisms that are imparted on the process.…”
Section: Frustule Genetic Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraordinary precision and frequency with which this mechanism occurs has always fascinated and intrigued biologists and different models have been proposed. However, to date none of them is able to explain biosilica morphogenesis in its entirety [109]. Indeed, there are still many components of the process that should be clarified, such as how this higher-order structure is formed and what are the exact spatial and temporal mechanisms that are imparted on the process.…”
Section: Frustule Genetic Modificationmentioning
confidence: 99%
“…Cloning technology for GFP fusion proteins. [109] One of the earliest examples of genetic engineering-based approach in the study of frustule biogenesis has been reported for T. pseudonana by Shrestha and Hildebrand in 2015 [121]. The authors, using Gateway technology for GFP fusion proteins and antisense RNA and RNA interference (RNAi) approaches, determined the spatial localization and the regulatory and signaling role for the individual silicon transporters genes (SITs).…”
Section: Cryptica Id G20669 (Sin1 Homologue)mentioning
confidence: 99%